ChemInform Abstract: Modulable and Highly Diastereoselective Carbometalations of Cyclopropenes. Issue 28 (15th July 2014) - Didier, Dorian; Delaye, Pierre‐Olivier; Simaan, Marwan; Island, Biana; Eppe, Guillaume; Eijsberg, Hendrik; Kleiner, Amir; Knochel, Paul; Marek, Ilan
Abstract It is found that cyclopropenyl derivatives of type (I) and (X) undergo Cu‐catalyzed carbomagnesiation with very high syn‐diastereoselectivity.